Organic Fertilizer Marketing Strategy - Juniartiningsih, Baiq Maya; Anwar, Khairil; Novida, Sari (Kompartemen: Kumpulan Orientasi Pasar Konsumen, 2023)
The issue of waste management is a significant concern in the NTB Province, Indonesia. Mataram City produces 314 tons of waste per day, with the majority (273 tons) being sent to landfills. Similarly, West Lombok Regency generates 175.4 tons of waste daily, with only 01.76 tons allocated for landfill disposal. Notably, Kebon Kongok landfill serves as a disposal site for both areas. In addressing this waste issue, the Lingsar Regional Integrated Waste Processing Site (TPST) has emerged as a vital player, employing Black Soldier Fly (BSF) Bioconversion Technology to process organic waste. This aligns with the government's flagship program of achieving zero waste in West Nusa Tenggara by efficiently managing, reducing, and utilizing waste, ultimately contributing to economic development. One key aspect of the study pertains to the organic fertilizer market strategy at the UPTD Regional Waste Landfill of NTB Province. It aims to understand the Price Effect (X1), the Promotion Effect (X2), and their combined influence on demand (Y) for organic fertilizer. The research employs a quantitative descriptive method conducted at the UPTD TPA Regional Waste province BSF Lingsar Unit, involving 30 farmer respondents. Data is analyzed using Regression Analysis and Multiple Correlation (Multiple Regression Analysis) through the SPSS Program. Results indicate that respondents exhibit a high perception of demand for organic fertilizer. The Multiple Linear Regression model showcases the effects of Price and Promotion strategies on Demand. The F Test (Anova) confirms that both strategies significantly impact demand. Further analysis reveals that the Price strategy (X1) has no significant individual effect on demand, while the Promotion strategy (X2) partially influences demand. The Coefficient of Determination Test (R2) indicates that Price and Promotion strategies jointly contribute 40.5% to the demand for organic fertilizer, leaving the remaining 59.5% influenced by other independent variables. This research underscores the importance of strategic pricing and promotion in driving demand for organic fertilizer in Lingsar District, West Lombok Regency, and the broader implications for waste management and economic development in the NTB Province.